Improvement of Chronic Rhinosinusitis and Reduction of the Myeloperoxidase-Antineutrophil Cytoplasmic Antibody Titer in a Patient with Eosinophilic Granulomatosis with Polyangiitis by Additional Mepolizumab - Tamechika, Shin-ya; Isogai, Shuntaro; Maeda, Shinji; Naniwa, Taio; Niimi, Akio (Case Reports in Rheumatology, 2021)
A case of eosinophilic granulomatosis with polyangiitis (EGPA) in which chronic rhinosinusitis (CRS) was improved with a reduction in the myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA) titer after the addition of mepolizumab is reported. A 55-year-old woman with EGPA receiving prednisolone 5 mg/day developed CRS with increases in the eosinophil count and the MPO-ANCA titer. Although it improved with prednisolone 15 mg/day in addition to mizoribine 150 mg/day, because azathioprine could not be taken orally due to side effects, it relapsed after prednisolone was tapered to 5 mg/day. There was no exacerbation of other vasculitis symptoms such as mononeuropathy multiplex. The patient was treated with additional mepolizumab 300 mg every 4 weeks, which resulted in the improvement of CRS and marked reductions of the eosinophil count and MPO-ANCA titer, and the reduction of prednisolone to 2 mg/day. Furthermore, even after tapering mepolizumab to 200 mg every 4 weeks, her condition remained stable without relapse of EGPA and without increases in the eosinophil count and MPO-ANCA titer. The clinical course of mepolizumab treatment in this patient suggests that the IL5-dependent inflammatory cascade is one of the factors contributing to the increase in MPO-ANCA in EGPA.